The frequency of depression and menopause-related symptoms in postmenopausal women living in a province in Eastern Turkey, and the factors that affect depressive status - Deveci, S. Erhan; Acik, Yasemin; Dag, Dilek Guenes; Tokdemir, Mehmet; Gundogdu, Cemal (Int Scientific Information, Inc, 2010)
Background: This study was designed to determine depression in women in the postmenopausal stage in Elazig city, located in Eastern Turkey, and determine the factors affecting depressive status. Material/Methods: The sample included 546 women and of these, 519 could be contacted. A questionnaire was con conducted with the women who were included in the study. This included demographic properties, which are thought to affect depression. Subjects were given the Beck Depression Inventory (BDI). Results: In total, 97.7% of women reported that they experienced a problem or had complaints during menopause, while 54.9% reported that they experienced problems in their sexual lives. The mean BDI score of women was 17.01 +/- 8.75. The ratio of women whose total scores were higher than the breakpoint of 17 was 42.2%. Single, widowed, and divorced women had higher ratios than mar married women; primary school or lower education women had higher ratios than high school or low lower education graduate women; the women who reported that they had problems in their sexual lives had higher ratios than the other women within the survey; the women who were subject to vi violence at any time during their lives had higher ratios than the women who had not experienced violence (P<.05). Conclusions: The frequency of depression symptoms in women living in Elazig is high. The information and services that the local women receive about menopause are inadequate.
Keywords: menopause; depression; effecting factors